Synthesis and characterization of mesoporous gamma-alumina by glucose as soft-template for molybdenum-99 adsorption: high and low molar ratio of water to aluminium isopropoxide effect. Issue 1 (December 2021) - Saptiama, I; Nurmanjaya, A; Rindiantono, F; Marlina,; Lestari, A M; Nugraheni, N F; Mujamilah,
Abstract: The mesoporous gamma-alumina is a good material for metal adsorption. Its textural properties are excellent, mainly for molybdenum-99 radioisotopes adsorption as part of 99 Mo/ 99m Tc generator in nuclear medicine. In this work, we have prepared mesoporous gamma-alumina by sol-gel treatment in the presence of glucose as a soft template. The molar ratio of reactant (water: aluminium isopropoxide(AIP)) was applied in the high and low ratios (150:1 and 25:1). The resulted mesoporous gamma-alumina was investigated using characterization analysis of X-ray diffraction, Nitrogen adsorption-desorption, and FTIR. The results indicate that the mesoporous gamma-alumina in the high molar ratio of water to AIP had a higher surface area and better crystallinity than the low molar ratio of reactants. Furthermore, in the Mo adsorption test, the mesoporous gamma-alumina with the high molar ratio posed a higher Mo adsorption capacity up to 55.69 mg Mo g −1 adsorbent. In the future, the molar ratio of reactants should be tuned in the range of around 150:1 to obtain the optimal Mo adsorption capacities of the resulted mesoporous gamma-alumina using the glucose template.